Analisis Perbandingan Ketelitian Dimensi Objek pada Pemodelan 3D Menggunakan GNSS Visual RTK dan Handheld Slam Lidar - Rini Aulia Ramadhani; Dwi Arini; Defwaldi Defwaldi; Ilham Armi (Asosiasi Riset Ilmu Teknik Indonesia, 2026)
Three-dimensional (3D) modeling has become an effective approach for documenting and measuring object dimensions in various geospatial applications. This study aims to evaluate the dimensional accuracy of 3D models generated using GNSS Visual RTK and Handheld SLAM LiDAR, with Total Station measurements used as the reference data. The research was conducted through field data acquisition using both technologies, followed by 3D model reconstruction and dimensional measurements on several parts of the building object. Dimensional accuracy was evaluated by comparing object dimensions and calculating the Mean Absolute Error (MAE) and percentage error. The results show that both technologies are capable of producing 3D models that accurately represent the dimensions of the object. However, GNSS Visual RTK demonstrated higher dimensional accuracy than Handheld SLAM LiDAR for most measurement parameters. These findings indicate that GNSS Visual RTK is more suitable for applications requiring high dimensional accuracy, whereas Handheld SLAM LiDAR offers advantages in faster data acquisition and more efficient mapping of larger areas.